Financial Smart Student Movement: Financial Literacy and Entrepreneurship Assistance Based on Practical Activities at SMPN 1 Pagu Kediri Regency - Efa Wahyu Prastyaningtyas; Elis Irmayanti; Bayu Surindra; Aning Maslikhah Azzamroh; Fenny Melianti Christine (International Journal of Community Service Implementation, 2026)
The Community Service Program (PKM) was held to improve financial literacy and entrepreneurial skills among students at SMP Negeri 1 Pagu. The results of observation and pre-test show that students' understanding of financial management is still low. Students are unable to distinguish between needs and wants, do not have the habit of recording their expenses, and do not understand the basics of entrepreneurship. This activity is carried out through the Participatory Action Research (PAR) approach, which includes the stages of problem identification, planning, training, mentoring, observation, and evaluation. The program includes financial literacy training, entrepreneurship training, simple business practices, and the use of digital media as marketing tools. Based on the results of the evaluation, there was a significant improvement in students' abilities. Post-tests showed that 81.6% of students were able to manage their pocket money well, 89.5% could distinguish between needs and wants, and 81.6% understood the concept of financial literacy. In addition, most students have started to get used to saving and show interest in entrepreneurial activities. Thus, this PKM program has proven to be effective in improving students' knowledge and skills related to financial literacy and entrepreneurship.